2017
DOI: 10.3390/ma10111269
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanical Properties of Al-Cu-Fe-X Alloys with Excellent Thermal Stability

Abstract: In this work, the structure and mechanical properties of innovative Al-Cu-Fe based alloys were studied. We focused on preparation and characterization of rapidly solidified and hot extruded Al-Cu-Fe, Al-Cu-Fe-Ni and Al-Cu-Fe-Cr alloys. The content of transition metals affects mechanical properties and structure. For this reason, microstructure, phase composition, hardness and thermal stability have been investigated in this study. The results showed exceptional thermal stability of these alloys and very good v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Nonetheless, the coatings are seen to effectively protect the AA2024 alloy (Figure 4 Generally, materials with more negative E cor are known to experience more significant corrosion damage and vice versa. Corrosion current density i cor is also indicative characteristic of the degree of the material degradation at corrosion attack [33,35,36,39,[45][46][47][48][49]. In this study, the i cor values were assessed using a Tafel fitting by the intersection of the tangent to cathodic polarization curve and the E cor level [39,44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the coatings are seen to effectively protect the AA2024 alloy (Figure 4 Generally, materials with more negative E cor are known to experience more significant corrosion damage and vice versa. Corrosion current density i cor is also indicative characteristic of the degree of the material degradation at corrosion attack [33,35,36,39,[45][46][47][48][49]. In this study, the i cor values were assessed using a Tafel fitting by the intersection of the tangent to cathodic polarization curve and the E cor level [39,44].…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that their hardness and wear resistance values are comparable to or even higher than that of the natural composites containing QC particles distributed in the bcc β-phase [25][26][27][28][29], multi-phase alloys, or artificial Al-based composite layers containing QC particles [30][31][32]. The corrosion resistance of the QC coatings was shown to be high and comparable with that of stainless steel [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hypoeutectic Al-Cu alloys with a relatively low percent of Cu should be considered. The addition of Ni increases the alloy strength, on the other side, the melting point starts to increase noticeably after passing the eutectic point 2.7 wt.% [18]. Moreover, the excess addition of Ni has no effect or negative effect on the strength of the alloy.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, understanding the interdiffusion mechanism and controlling the degree of IC formation at the Al/Cu interface are critical for good thermal conductivity. Školáková et al reported that the mechanical strength and hardness are influenced by the presence of the CuAl 2 phase [ 17 ]. The phases are very stable and when this phase is contained in the aluminum alloys could be precipitated during heat treatment and improve thermal properties [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%